1986
DOI: 10.1073/pnas.83.21.8258
|View full text |Cite
|
Sign up to set email alerts
|

Genetic construction, expression, and melanoma-selective cytotoxicity of a diphtheria toxin-related alpha-melanocyte-stimulating hormone fusion protein.

Abstract: The structural gene for diphtheria toxin, tox, has been modified at its Sph I site by the introduction of an oligonucleotide linker encoding a unique Pst I restriction endonuclease site and a synthetic oligonucleotide encoding a-melanocyte-stimulating hormone (a-MSH). The resulting fusion gene directs the expression of a diphtheria toxin-related a-MSH hybrid protein in which the diphtheria toxin receptorbinding domain has been replaced with a-MSH sequences. The chimeric toxin has been partially purified from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 41 publications
(14 reference statements)
0
56
0
Order By: Relevance
“…Besides the pigmenting effect, MSH has also been shown to act as a neurotransmitter in the central nervous system [5], as an endocrine stimulant [6] and as a modulator of immune inflammatory responses [7]. The hormone is considered a potential tool in the diagnosis and therapy of melanoma as it has been used in conjugation with cytotoxin [8] ~r:,~ cytotoxic T-cells [9] for killing melanoma cells by recognizing their MSH receptors. Recently it has been shown that MSH can increase intracellular calcium and activate protein kinase C [10].…”
Section: Introduction Melanocyte Stimulating Hormone (Msh) Is a Stronmentioning
confidence: 99%
“…Besides the pigmenting effect, MSH has also been shown to act as a neurotransmitter in the central nervous system [5], as an endocrine stimulant [6] and as a modulator of immune inflammatory responses [7]. The hormone is considered a potential tool in the diagnosis and therapy of melanoma as it has been used in conjugation with cytotoxin [8] ~r:,~ cytotoxic T-cells [9] for killing melanoma cells by recognizing their MSH receptors. Recently it has been shown that MSH can increase intracellular calcium and activate protein kinase C [10].…”
Section: Introduction Melanocyte Stimulating Hormone (Msh) Is a Stronmentioning
confidence: 99%
“…For therapeutic or diagnostic purposes, ligands such as growth factors or the Fv fragments of antibodies are fused to bacterial toxins, (3-lactamase, or alkaline phosphatase, which display useful enzymatic activity when bound to the target cells (1)(2)(3)(4)(5). Also, bifunctional ligands have been created by fusing interleukin 2 (IL2) with IL6, granulocyte/macrophage-colony-stimnulating factor (GM-CSF) with IL3, and IL2 with recombinant antibody fragments (6)(7)(8).…”
mentioning
confidence: 99%
“…This dream was realized almost a hundred years later by Murphy et al (1986) with the design and synthesis of DT based fusion protein toxins that were targeted toward specific eukaryotic cell receptors. Substitution of the native R domain with a surrogate ligand results in the formation of a fusion protein toxin construct that targets cells expressing the appropriate cell surface receptor.…”
Section: Receptor Bindingmentioning
confidence: 99%